Оцінка внутрішнього підприємницького клімату в підприємствах торгівлі - Краснокутська, Наталія Станіславівна; Бубенець, Ірина Георгіївна; Артеменко, Віктор Станіславович (Харківський державний університет харчування та торгівлі, 2015)
Проаналізовано та узагальнено результати оцінки складових внутрішнього підприємницького клімату за підсумками проведеного анкетування. Визначено, що формування сприятливого підприємницького середовища хоча й не гарантує розвиток усіх складових підприємницького потенціал у, але сприяє його активізації. Запропоновано розрахунок рівня сприятливості підприємницького клімату.

At present the problem of entrepreneurial activity development and entrepreneurial potential formation is rather important. The entrepreneurial potential of the enterprise is determined by the possibilities of its owners and personnel concerning the support and expansion of their entrepreneurial activity according to the adopted purposes. The tools of entrepreneurial potential activation influence the choice of the priorities of the development specify the scale of trade enterprises activity and need constant study. Formation and development of entrepreneurial potential is a necessary condition for the creation of stable competitive preferences. In such context the diagnostics of internal entrepreneurial climate in trade enterprises becomes a mandatory function of modern management and its purpose is to reveal the level of the activities of retail business workers’ regarding the realization of own entrepreneurial possibilities, internal factors promoting or restraining such possibilities. The aim of the article is to specify the directions characterizing interior entrepreneurial climate. Its evaluation in trade enterprises is directed towards the reveal and activation of entrepreneurial potential on the grounds of calculations of the level of assistance of entrepreneurial climate. The directions for the evaluation of entrepreneurial climate ( flexibility of the structure; level of the development of organizational culture oriented towards the risks; strategic attitude to innovations; the velocity of making decisions; HRpractices for the support of creative potential) are defined, and its evaluation by the level of assistance in trade enterprises is carried out. The results of the research demonstrated that entrepreneurial climate assistance was low for most of the trade enterprises was low, but the weakest positions are the speed of making decisions and weakness of HR-practices regarding the support and development of creative and innovative potential of employees. Based on the received results it is specified that the formation of favorable entrepreneurial environment slightly guarantees the development of all components of entrepreneurial potential promotes its activation.
Evaluation of internal entrepreneurial climate in trade enterprises
Keywords: підприємництво; потенціал; підприємство; торгівля; підприємницький клімат; entrepreneurship; potential; assessment; enterprise; trade; business climate